Morfologia, taxonomia e filogenia de novos espécimes de archosauromorpha do triássico inferior do Rio Grande do Sul - Oliveira, Tiane Macedo de (2023)
The Sanga do Cabral Formation (Lower Triassic, Rio Grande do Sul) has received particular attention in recent years, revealing a previously hidden diversity, especially concerning archosauromorph records. In addition to them, the fossil record of the Sanga do Cabral Formation comprises procolophonids and temnospondyl amphibians. The main objective of this thesis is to describe new specimens of archosauromorphs discovered in rocks from the Lower Triassic in Rio Grande do Sul, Brazil. These materials were recovered from the locality ‘Bica São Tomé’, belonging to the Sanga do Cabral Formation. The specimens are represented by isolated materials related to Archosauriformes (cervical vertebra UNIPAMPA 750, dorsal vertebra UNIPAMPA 271, neural spine UNIPAMPA 686, and a portion of the cranial roof UNIPAMPA 681), and a reasonably complete and articulated postcranium of an archosauromorph (UNIPAMPA 653). The isolated materials are attributed to cf. Proterosuchus and cf. Chasmatosuchus, representing the first conclusive records of proterosuchids for the Early Triassic of Brazil, while UNIPAMPA 653 is composed of vertebrae (cervical, dorsal, sacral, and caudal), bones from the shoulder and pelvic girdle, and both forelimbs and hindlimbs, and is attributed to the holotype of Teyujagua paradoxa, comprising the most complete specimen for the Sanga do Cabral Formation. Together with other tetrapods previously reported for the unit, these records enhance our knowledge of biotic diversification during the early Triassic and contribute to our understanding of Archosauromorpha diversification after the Permian-Triassic extinction.